Soil bio-functioning under Acacia nilotica var. tormentosa protected from forest along the Senegal river - Faye, A; Sall, S.N.; Chotte, Jean-Luc; Lesueur, Didier (Springer, 2007)
Acacia nilotica var. tomentosa trees from the Diarra protected forest located in the Senegal River valley were identified for the assessment of both biological nitrogen fixation, using the natural abundance method, and soil bio-functioning parameters (nodulation, root biomass, total microbial biomass, and potential N mineralization). The presence and the genetic diversity of indigenous rhizobia nodulating A. nilotica var. tomentosa was also investigated, taking into account distance from the trunk (0, 1, 2, and 3 m) and depth (0 25, 25 50, and 50 75 cm). Surprisingly, no nodules on the trees root systems were found, whereas under laboratory conditions the presence of indigenous rhizobia nodulating A. nilotica var. tomentosa was demonstrated in the analyzed soils (90% of the nodules harvested on the trapped plants were occupied by the same Inter-Genic Spacer (IGS) group, IGS1). There was no significant influence of trees and/or depth on total microbial biomass and potentials of nitrogen mineralization. Some assumptions were formulated on the possible combined effect of flooding, which usually occurs annually during 4 7 months, and the clayey soils in the Diara forests. Although a deeply natural nodulation of A. nilotica var. tomentosa trees by indigenous rhizobia is not excluded, but it still remains to be demonstrated.